EKSPRESI ESTETIS DAN MAKNA SIMBOLIS KESENIAN LAESAN - Kusumastuti, Eny (Harmonia: Journal of Arts Research and Education, 2009)
Laesan art is a kind of traditional art, which is a result of aesthetic expression of people with trancephenomenon in side. Here, implicit symbols occur in Laesan art, then it is interpreted by theaudiences and applied in terms of behavior patterns of people in Bajomulyo. From that phenomenon,research studies are form of aesthetic expression and meaning of symbols of Laesan art. Thisresearch uses qualitative approach, with data collection technique done by interview, observation ofparticipants, and documentation study. Analyzing data done by reducing, clarifying, decrypting,concluding, and interpreting all information selectively. Techniques of checking relevance data weredependability and conformability. Research result show that Laesan art having aesthetic expressionin: a) in the beginning, core, and the end of the show, b) supporting substance of the show consist ofperformance equipments; dance movement; offbeat; make up and clothing; and stages. Symbol thatshape meaning in the process of symbolic interaction consists of incense, offerings, accompaniedsing, and meaning of trance in Laesan. Suggested that Laesan art need to be repackaged in order tomake it better and have a high sale price, it is need to be conserved and inherited to the nextgeneration to avoid extinction.Kata Kunci : laesan, laes, ekspresi estetis, makna simbolis, trance